Association of Excessive Screen Time in Children with Language Delay During Covid-19 Pandemic: A Systematic Review - Ghaisani, Ulima Mazaya; Salam, Amalia Rasydini (Jurnal Psikiatri Surabaya, 2022)
AbstractBackground: Covid-19 pandemic and the associated of lockdown have confined children to their homes and have resulted in an exponential increase of screen use in children. The environment in which the child grows may either stimulate or inhibit their development in such a sensitive period. Language development of children starts early in infancy and surges in 2 years of life, updated knowledge about association of language delay with its aggravating risk factor, such as excessive screen time. Aim: scrutinize the association of increased risk of language delay in children under two years old with any screen time or screen time more than 1 hour in children 2-5 years old. Method: We make clinical question. We include studies from PubMed and Google Scholar on January 13th 2022. In the end, we have got three full reading articles. Result: Full reading article by Hauvel et al (2019), Varadarajan S et al (2021), and Collet M et al (2019) were choosen to discuss in this article review. Study by Hauvel et al (2019) and Varadarajan S et al (2021) describe that having screen time more than the recommendation from AAP would lead to delay language domain. Collet M et al (2019) found that children that had screen time before go to school and never discuss to their parents about what they are watching would have 6 time risk for develop primary language disorder. Conclusion: There is a correlation between excessive screen time in children and language delay.Keywords: covid-19, children, language delay, pandemic, screen time